2015
DOI: 10.1097/prs.0000000000001591
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgery and the Hypercoagulable State

Abstract: Hypercoagulability can pose a significant problem in microsurgical reconstruction. Here, the authors provide a comprehensive review of macrovascular and microvascular clotting phenomena from the unique viewpoint of two microsurgeons and a hematologist. The authors review the literature surrounding prevention of microvascular clots and provide an extensive discussion of hereditary thrombophilia. The authors also make explicit recommendations regarding the utility of thrombophilia testing and preoperative and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 58 publications
0
72
0
Order By: Relevance
“…[21][22][23][24][25][26][27] Nevertheless, ongoing controversy regarding the safety and effectiveness of these drugs in microsurgical patients is reflected in the wide variation of protocols reported by individual surgeons and high-volume centers. 6,14,19,[27][28][29][30] Although several experimental studies have documented improved microvascular patency with multiple pharmacologic agents, these findings have not consistently translated to lower rates of thrombosis/flap failure in subsequent human trials. [27][28][29][30][31][32][33][34][35] One explanation for this discrepancy may relate to the use of animal models that overestimate the thrombogenic risk encountered in most clinical situations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[21][22][23][24][25][26][27] Nevertheless, ongoing controversy regarding the safety and effectiveness of these drugs in microsurgical patients is reflected in the wide variation of protocols reported by individual surgeons and high-volume centers. 6,14,19,[27][28][29][30] Although several experimental studies have documented improved microvascular patency with multiple pharmacologic agents, these findings have not consistently translated to lower rates of thrombosis/flap failure in subsequent human trials. [27][28][29][30][31][32][33][34][35] One explanation for this discrepancy may relate to the use of animal models that overestimate the thrombogenic risk encountered in most clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports and our own experience indicate that microthrombotic events in hypercoagulable patients are multifactorial and dependent on the synergistic interactions of various genetic and environmental factors that influence clot formation. 5,6 A recent review by Pannucci et al 14 points to the presence of acquired factors, such as malignancy, trauma, and/or a personal history of venous thromboembolism (VTE), as the primary determinant of microvascular risk in thrombophilic patients. This observation is supported by retrospective data that demonstrate a relative absence of microvascular compromise in the setting of isolated hereditary thrombophilia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pannucci et al have reported good results with the use of antithrombotic therapy for high-risk patients. 21 Their practice is to use intravenous unfractionated heparin, run at 800 U/h during the operation and for 24 hours after surgery. Subsequently, the patient is started on prophylactic-dose enoxaparin, which is continued at least until discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Nonmodifiable risk factors, including age, BMI, malignancy in general, as well as tumor-related factors and therapy (e.g., tamoxifen), are beyond the control of the reconstructive surgeon or have no acceptable alternatives. [41][42][43] Modifiable risk factors, on the other hand, represent opportunities for the care team to reduce risk. Of particular interest are opportunities to reduce the operative duration and minimize hypercoagulability via chemoprophylaxis.…”
Section: Discussionmentioning
confidence: 99%